2015
DOI: 10.3928/00220124-20141122-01
|View full text |Cite
|
Sign up to set email alerts
|

Using Simulation Technology to Identify Gaps Between Education and Practice Among New Graduate Nurses

Abstract: Applied knowledge was observed among nurse groups from a medical-surgical residency program to measure clinical performance during simulation training. Twenty groups of new graduate nurses were observed during five simulated clinical scenarios, and their performances were scored on a 24-item checklist. Nurse groups showed significant improvement (p < 0.001) in applied knowledge in four clinical domains from week 1 to week 5, and the results provided valuable information of the groups' overall performances. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Everett-Thomas, Valdes, Fitzpatrick, & Birnback [5], discuss the need for standardized training programs to transition the new graduate nurse. The simulation design included five conditions that included acute onset of myocardial infarction, hyperglycemic crisis, hypoglycemic crisis, sudden cardiac arrest and heart failure with severe respiratory distress.…”
Section: Practice Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Everett-Thomas, Valdes, Fitzpatrick, & Birnback [5], discuss the need for standardized training programs to transition the new graduate nurse. The simulation design included five conditions that included acute onset of myocardial infarction, hyperglycemic crisis, hypoglycemic crisis, sudden cardiac arrest and heart failure with severe respiratory distress.…”
Section: Practice Recommendationsmentioning
confidence: 99%
“…While this is an ongoing dilemma in nursing education, healthcare leaders must Research done by Everett-Thomas, Valdes, Fitzpatrick, Rosen, and Birnback [5], shows that nurse residency programs can actually reduce costs associated with training new nurses through retention. Their study showed that with the incorporation of simulation to provide new nurses with five basic scenarios, new onset of myocardial infraction, hypoglycemic and hyperglycemic episodes, cardiac arrest and heart failure with severe respiratory distress could reduce turnover rates of new nurses by 30%.…”
Section: Significance Of Practice Problemmentioning
confidence: 99%
See 3 more Smart Citations